2021
DOI: 10.1097/jte.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Site Visits: Exploring the Perspectives of the Director of Clinical Education

Abstract: Introduction. Best practice in clinical education (CE) includes the formation of strong relationships through collaborative communication among all stakeholders. Directors of Clinical Education (DCEs) may establish this through a site visit (SV) during student CE experiences (CEEs) but several barriers to conducting SVs have been identified, including scheduling of visits, time, and cost. There is sparse literature describing the DCEs most preferred method of communication when conducting SVs. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(69 citation statements)
references
References 31 publications
5
64
0
Order By: Relevance
“…15-18 CI perceptions of academic program commitment were higher by those who received on-site visits, and these visits are also preferred by PT students and DCEs. 19,20 Additionally, this study found that alum status among participants had an overall positive effect on perceptions of partnership.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…15-18 CI perceptions of academic program commitment were higher by those who received on-site visits, and these visits are also preferred by PT students and DCEs. 19,20 Additionally, this study found that alum status among participants had an overall positive effect on perceptions of partnership.…”
Section: Discussionmentioning
confidence: 58%
“…However, the qualitative results demonstrated that on-site visits improved perceptions of communication, and this is in line with previous research findings. 7,8,19,20 e role of alum status may be the biggest contributing factor to perceptions of partnership among the variables included in the analysis. ere were higher perceptions of partnership with alums in the subcategories of trust, information sharing, and communication quality as well as in the aggregated partnership attributes and communication behaviors compared with nonalums.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations